Gangguan Berbahasa pada Tokoh Bertie dalam Film The King’s Speech (2010) - Halimah Fadilah (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2021)
This study aims to describe and examine the causes, forms, and treatment of stuttering experienced by Bertie's character in the film The King's Speech. This study uses a qualitative method by listening to the film The King's Speech and noting important things related to the material to be studied. From the results of the study it was found that Bertie experienced stuttering which was probably caused by the retraining she did as a child, as well as psychological factors because since childhood she had been pressured by many rules in the kingdom. The forms of stuttering experienced are repetition and blocking, and the most dominant form of stuttering is blocking. The treatment that Lionel, the therapist does, is to train the breathing mechanism and instill confidence in Bertie. Although his stuttering did not go away completely, Bertie was able to read speeches to his subjects with proper breathing and pauses.